IMPACT OF CLIMATE CHANGE ON HEALTH COST: A CASE STUDY OF LAHORE, PAKISTAN - Muhammad Tayyab (International Journal of Contemporary Issues in Social Sciences, 2024)
This study analyzes the impact of Climate Change12 on health in Lahore. The data have been collected from selected hospitals of Lahore. The study focuses on rising Climate Change and health. The data of cardiovascular diseases (indicator of state of health) from different hospitals of Lahore have been collected to assess the relationship between health and Climate Change. The study has found inverse relationship between cardiovascular diseases and Climate Change for Lahore. This study also calculated the direct and indirect cost of cardiovascular diseases (CVD) for Lahore. The findings of this study show that direct cost of CVD is much larger then indirect cost. However indirect cost is higher then the medicine cost while less then the total cost of cardiovascular diseases.